ENGLISH-ISLAMIC DIRECTIVES OF INTERFAITH DIALOGUE - Meraj Ahmad Meraj (دی اسکالر)
Interfaith dialogue is an endeavor of the followers of different religions to recognize the common phenomena in various religions in a bid to proceed towards the common goal of communal harmony. The objective of interfaith dialogue is to create mutual understanding and respect to work in unity for peace and prosperity of humanity without harming the identity of any religious group in multi-culture societies. It is believed that every religion has some universal values which can serve as a common ground with other religions. Islam, as a complete code of life, guides us in this regard too with clear directives. The Islamic directive is to engage in interfaith dialogue and cooperative relationships with the people of other faiths on the basis of what they have common between them as religious injunctions aiming at the betterment of society. We are living in a globalised world, with diverse religious, ethnic, cultural, social, economic and political backgrounds. The followers of various religions need to learn how to live together like members of one united big family in this small global village of ours, known as the world. All these aspects suggest the importance for a better understanding one another through interfaith dialogue. The aim of this paper is to discuss all the possible ways to strengthen interfaith dialogue to resolve inter-religious conflicts and to restore harmony and peace in the light of Islamic directives. This paper also explores the role of Islamic directives to find a common theological platform with adherents of different faiths to create a better and peaceful pluralistic society.